2017
DOI: 10.1371/journal.pone.0180028
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of zinc preconditioning against renal ischemia reperfusion injury is dose dependent

Abstract: ObjectivesIschemia-reperfusion injury (IRI) is a major cause of acute kidney injury and chronic kidney disease. Two promising preconditioning methods for the kidney, intermittent arterial clamping (IC) and treatment with the hypoxia mimetic cobalt chloride, have never been directly compared. Furthermore, the protective efficacy of the chemically related transition metal Zn2+ against renal IRI is unclear. Although Co2+ ions have been shown to protect the kidney via hypoxia inducible factor (HIF), the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
1
36
1
1
Order By: Relevance
“…Glomerular capsule and vessel loops damage were also observed in nephrotic syndrome due to excessive protein loss via the damaged glomerular filtration barrier (Hall et al, 1986;Tesar et al, 1994). Moreover, Rao et al (2017) found also focal tubular dilation, flattening and attenuation of the epithelium, loss of the luminal brush border, apoptotic tubular…”
Section: Discussionmentioning
confidence: 91%
“…Glomerular capsule and vessel loops damage were also observed in nephrotic syndrome due to excessive protein loss via the damaged glomerular filtration barrier (Hall et al, 1986;Tesar et al, 1994). Moreover, Rao et al (2017) found also focal tubular dilation, flattening and attenuation of the epithelium, loss of the luminal brush border, apoptotic tubular…”
Section: Discussionmentioning
confidence: 91%
“…Such observation was not detected in female. The protective effect of Zn in kidney injury may be dose and gender related 34,39 , and actually the involved mechanisms is not well clear. Some of the renal function markers also were different between genders.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the role of gender or sex hormones in kidney toxicity induced by other drugs, such as cisplatin and gentamicin, have been documented [22][23][24][25][26][27][28][29][30][31][32][33] , although their mechanisms have not been completely understood. In addition, the antioxidant supplements, such as zinc (Zn), have been widely used in laboratory research to protect the kidney against injury [34][35][36][37][38][39][40][41][42] . It seems that the administration of this trace element Zn could be considered as a safe protective agent for transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In these cases, evidence suggesting supplementation with antioxidant and anti-inflammatory micronutrients such as zinc can form antioxidant defense mechanisms, downregulate cytokine production, and decline cytokine concentrations and hence can reduce oxidant injury to cells and organs. [ 3 4 ] Since several renal diseases are mediated by oxidant injury, decreasing the production of reactive oxygen molecules or treating with antioxidant agents may open new avenues for research into therapeutic intervention. [ 5 ]…”
mentioning
confidence: 99%
“…It can antagonize the transition of metal-catalyzed reactions and reduce the formation of hydroxyl radical from hydrogen peroxide. [ 4 ] However, its effectiveness has not been tested in a trial regarding CS-associated AKI. Berger et al .…”
mentioning
confidence: 99%